Towards understanding of unconventional kinetochores in kinetoplastids - Ludzia, P (2021)
The kinetochore is the macromolecular protein machinery that drives chromosome segregation by interacting with spindle microtubules. Kinetoplastids, an evolutionarily divergent group of eukaryotes, possess a unique set of kinetochore proteins (KKT1—20, 22—25 and KKIP1—12) that lack significant similarity to known kinetochore components in other eukaryotes.